ANALISIS PERILAKU HARIAN HARIMAU SUMATERA (Panthera tigris sumatrae) DI TAMAN MARGASATWA MEDAN - Kiandreas Tarigan; Wawan Nurmawan; Martina A. Langi (COCOS, 2021)
AbstractMedan Wildlife Park is a conservation area for the Sumatran tiger (Panthera tigrissumatrae) which is kept in an artificial environment and shown to the public. Differentenvironments will affect the daily behavior of animals, and an indicator of successfulconservation is seen from the increase in the number of tigers that survive and are ableto breed (Yelanda, 2017). This research aims to study the daily behavior of thesumatran tiger (Panthera tigris sumatrae) at the Medan Wildlife Park by calculating2the duration and frequency of occurrence of each behavior sumatran tigers (Pantheratigris sumatrae) in the Medan Wildlife Park. The results of this study indicate that thereare five behaviors of the sumatran tiger (Panthera tigris sumatrae) in the MedanWildlife Park, with the percentage of duration and frequency of behavior from thehighest to the lowest is resting behavior (49.23%) with a relative frequency of 41.48%,moving places ( 41.02%) with a relative frequency of 37.47%, others (4.94%) with arelative frequency (12.71%), social (2.60%) with a relative frequency of 4.39%, andeating ( 2.20%) with a relative frequency of 3.95%. The daily behavior of the Sumatrantiger has differences in terms of length of time, manner, and behavior in the MedanWildlife Park with behavior in the wild. Based on the different tests conducted, it isknown that male and female sumatran tigers (Panthera tigris sumatrae) have differentforms of behavior but do not have a significant difference in behavior duration.Keywords: daily behavior, sumatran tiger (Panthera tigris sumatrae), medan wildlifepark